2023
DOI: 10.1002/adfm.202307002
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Bonding Behavior of d‐p Orbitals to Enhance Oxygen Reduction through Push–Pull Electronic Effects

Qi Jing,
Zhiyuan Mei,
Xuelin Sheng
et al.

Abstract: The regulation of electronic structure is intricately linked to the intrinsic activity of oxygen reduction. Herein, a strategy for electronic structure modulation induced by bimetallic push–pull electronic effects in dual‐atom catalysts (Fe,Ni/N‐C@NG) is developed. Experiments and theoretical analysis reveal that Fe sites exhibit favorable bonding behaviors (Fe–O: dxz‐p, dyz‐p, and dz2‐p) and spin configurations, which can enable rapid desorption of *OH and thus enhance the intrinsic activity of oxygen reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These findings indicated that the coordination induced by SDS led to a high‐spin state of FNS‐400. On note, the comparison of the high‐resolution Ni 2p XPS spectra of FNS and FNS‐400 revealed a much higher ratio of Ni 2+ /Ni 3+ in FNS‐400 (0.97) than in FNS (0.11) (Table S2), further confirming that the high‐spin configuration of FNS‐400 benefited from the high‐spin state of Fe 3+ [5a,11] . To further confirm the spin state details of Fe, 57 Fe Mössbauer spectra (Figure S9) were collected at room temperature.…”
Section: Resultsmentioning
confidence: 91%
“…These findings indicated that the coordination induced by SDS led to a high‐spin state of FNS‐400. On note, the comparison of the high‐resolution Ni 2p XPS spectra of FNS and FNS‐400 revealed a much higher ratio of Ni 2+ /Ni 3+ in FNS‐400 (0.97) than in FNS (0.11) (Table S2), further confirming that the high‐spin configuration of FNS‐400 benefited from the high‐spin state of Fe 3+ [5a,11] . To further confirm the spin state details of Fe, 57 Fe Mössbauer spectra (Figure S9) were collected at room temperature.…”
Section: Resultsmentioning
confidence: 91%
“…It subsequently promotes the reduction of the bond sequence of * OH on Fe (II) from LS to MS (Figure 4e). [ 54,55 ] In this way, the adsorption of * OH on Fe SA/AC @HNC will be weaken, by which the kinetics of ORR could be boosted. Next, electron transfer behaviors were examined by charge density difference and Bader charge (Figure 4f; and Figure S41, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…S12d †), indicating that the incorporation of B has a certain impact on the electronic structure of both Ni 5 P 4 and Ni 2 P phases. Before B is doped, the t 2g orbit of the d orbital of the Ni site is completely occupied, so there is an initial electron repulsion between Ni and P. 21 After B replaces part of P, the electronegativity of B is weaker than that of P, causing a rearrangement of the electronic structure around Ni (Fig. 3g and h).…”
Section: Papermentioning
confidence: 99%